2009
DOI: 10.1007/s12221-009-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fatigue properties of prototype textile components of endovascular devices

Abstract: The fatigue resistance of twelve tubular textile samples designed for use in prototype endovascular devices was tested by an accelerated fatigue tester. Three time points were selected, namely 0, 26×10 6 , and 100×10 6 cycles, which are equivalent to 0, 10 months, and 38.5 months implanted in the human body. Changes in tubular diameter, woven fabric count, thickness, mass per unit area, porosity, water permeability, and bursting strength were selected to characterize the performance of these samples before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…[ 29 ] Thus, to suppress the aggregation of conjugated groups and enhance photoluminescence efficiencies are also the important ways for exploring the practical application of luminescent materials. [ 30 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 29 ] Thus, to suppress the aggregation of conjugated groups and enhance photoluminescence efficiencies are also the important ways for exploring the practical application of luminescent materials. [ 30 ]…”
Section: Methodsmentioning
confidence: 99%
“…It is seen from Figure 2 that the changes in porosity of the PTT samples with 75D/72f filament as weft yarns are greater than that with 55D/24f filaments. Filaments inside the multifilament yarns may spread or accumulate under the influence of pulsatile pressure applied on each yarn [13]. The larger the yarn size, the more rigid the sample, and the more easily they creep or deform plastically.…”
Section: Characterization Of Fatigue Performancementioning
confidence: 99%
“…Intrinsic structural failure of Dacron® prostheses is a late exceptional complication, resulting from a loss of structural integrity of the graft [12]. Zhao et al [13] tested woven PET tubular textile samples by an accelerated fatigue tester in vitro. The results showed that there were clearly observable relationships between the change in textile parameters and fatigue performance of the samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations